China's new governing party paradigm political renewal and the pursuit of National Rejuvenation - Heath, Timothy R. (Rethinking Asia and international relations, 2014)
For the first time since its founding in 1921, the Chinese Communist Party (CCP) has adopted a new paradigm for its role in China. Abandoning its former identity as a 'revolutionary party', the CCP now regards itself as a 'governing party' committed to meeting the diverse needs of its people and realizing China's revitalization as a great power. Few studies are available on the CCP's adoption of this new identity and of its political implications. This book remedies that oversight by explaining the historic context, drivers, and meaning of the governing party paradigm